Multifunctional Film Assembled from N-Doped Carbon Nanofiber with Co–N4–O Single Atoms for Highly Efficient Electromagnetic Energy Attenuation - Xu, Jia; Li, Bei; Ma, Zheng; Zhang, Xiao; Zhu, Chunling; Yan, Feng; Yang, Piaoping; Chen, Yujin (Nano-Micro Letters, 2024)
Single-atom materials have demonstrated attractive physicochemical characteristics. However, understanding the relationships between the coordination environment of single atoms and their properties at the atomic level remains a considerable challenge. Herein, a facile water-assisted carbonization approach is developed to fabricate well-defined asymmetrically coordinated Co–N4–O sites on biomass-derived carbon nanofiber (Co–N4–O/NCF) for electromagnetic wave (EMW) absorption. In such nanofiber, one atomically dispersed Co site is coordinated with four N atoms in the graphene basal plane and one oxygen atom in the axial direction. In-depth experimental and theoretical studies reveal that the axial Co–O coordination breaks the charge distribution symmetry in the planar porphyrin-like Co–N4 structure, leading to significantly enhanced dielectric polarization loss relevant to the planar Co–N4 sites. Importantly, the film based on Co–N4–O/NCF exhibits light weight, flexibility, excellent mechanical properties, great thermal insulating feature, and excellent EMW absorption with a reflection loss of − 45.82 dB along with an effective absorption bandwidth of 4.8 GHz. The findings of this work offer insight into the relationships between the single-atom coordination environment and the dielectric performance, and the proposed strategy can be extended toward the engineering of asymmetrically coordinated single atoms for various applications. Highlights: 1 Asymmetrically coordinated Co–N4–O sites on N-doped carbon nanofiber were prepared. 2 Co–O coordination along the axial direction led to enhanced dielectric polarization loss. 3 Multifunctional films were developed for practical application in harsh environments.